Seismic Behavior Analysis of the Bank Slope Considering the Effect of Earthquake-Induced Excess Pore Water Pressure - Huang, Shuai; Zhai, Shufeng; Liu, Yingjie; Liu, Chuanzheng; Goda, Katsuichiro; Mou, Ben (Frontiers in Earth Science, 2021)
Soil slopes, located near rivers or the sea, often get damaged dramatically under seismic action due to the high groundwater level. To determine the failure mechanism, this study proposed an analytical method for a composite critical slip surface of a multi-layer slope considering the effects of the excess pore water pressure using the Newmark’s method and variational principle. Based on this, a method for evaluating the effects of the excess pore water pressure on the permanent displacement of the slope under seismic action was established, and influence mechanisms of the excess pore water pressure on failure modes of the multi-layer bank slope at different groundwater levels were studied. The research results show that slip surfaces basically have same shapes at different groundwater levels; however, with the rise of the groundwater level, soil above a seepage line is not affected by the excess pore water pressure, and its sliding scale slightly changes. For soil below the seepage line influenced by the excess pore water pressure, the slip surface constantly extends to the interior of the slope, resulting in the increase in the sliding scale. Due to the cumulative increase in the excess pore water pressure, the bank slope at different groundwater levels is generally manifested as shear sliding at the slope toe and tensile fracture at the top. Finally, based on the shaking table test, the proposed method was verified to be reasonable and accurate. This research provides a simple and reliable method for slope engineering technicians to evaluate the stability of water-rich soil slopes.